2009
DOI: 10.1016/s0377-1237(09)80095-6
|View full text |Cite
|
Sign up to set email alerts
|

Root Canal Treatment Using Thermoplasticized Carrier Condensation Technique

Abstract: Background: The management of pulpally and apically infected teeth has evolved into a modality of conservation with predictable degree of success.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(29 citation statements)
references
References 19 publications
0
29
0
Order By: Relevance
“…2 ). The pain assessment was adopted from our previous study which measured pain on a 10-point Likert scale, ranging from no pain (score 0) to extreme pain (score 10) [ 16 ]. The patients were asked to attend regular follow-ups every 6 months after the endodontic treatment.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…2 ). The pain assessment was adopted from our previous study which measured pain on a 10-point Likert scale, ranging from no pain (score 0) to extreme pain (score 10) [ 16 ]. The patients were asked to attend regular follow-ups every 6 months after the endodontic treatment.…”
Section: Methodsmentioning
confidence: 99%
“…When doubt existed as to whether pathological periapical conditions were present or not, the case was classified as normal. The method of radiographic assessment for the length and density of the root canal filling were recorded for analysis [ 16 ]. The length of the root canal filling were recorded as 1) adequate – filling within 2 mm from radiographic apex, 2) overfilling – filling over radiographic apex or 3) underfilling – filling at least 2 mm short from apex.…”
Section: Methodsmentioning
confidence: 99%
“…Dental practitioners use it often, and it frequently serves as a basis of comparison for new obturation techniques [ 4 ]. The core carrier obturation technique has become popular since its introduction in late 1980s, as studies have generally found that it as effective as CLC for root canal obturation [ 4 6 ]. In addition, many clinicians consider it to be fast, predictable, easy to use, effective, and useful for small, curved, or densely packed canals [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…They were evaluated for their methodology and risk of bias (Table 1 ). Among these 19 studies, 11 papers reported the treatment success [ 1 , 15 , 19 , 20 , 25 31 ], eight papers reported short-term (within 7 days) postoperative pain [ 17 , 19 , 25 , 27 , 28 , 32 34 ], 11 papers reported overfilling [ 15 , 17 , 19 , 20 , 25 , 27 , 30 , 35 – 38 ] and seven papers reported the adequate adaptation of root canal filling [ 15 , 20 , 25 , 30 , 35 , 37 , 38 ].
Fig.
…”
Section: Resultsmentioning
confidence: 99%
“…The adaptation of the obturation material was regarded as adequate when it was uniformly filled without visible voids or canal spaces in radiographic assessment. There was no consensus in reporting the time used for obturation in the studies and a summary was performed without statistical analysis [ 19 , 20 ].…”
Section: Methodsmentioning
confidence: 99%